The tide that does not raise all boats: An assessment of EU preferential trade policies - Cipollina, Maria; Laborde Debucquet, David; Salvatici, Luca (International Food Policy Research Institute, 2014)
The aim of this paper is to assess of the impact of the European Union’s trade preferences on global trade, focusing on several methodological issues that are relevant to the trade-creating impact of these preferences. Using highly disaggregated eight-digit data in a theoretically grounded gravity model framework, we define an explicit measure of preferential tariff margins computed on alternative definitions based on a comparison between bilateral applied tariffs and two different reference levels: the most favored nation duty and a constant elasticity of substitution price aggregator. From the methodological point of view, we show that assessing the impact of these policies can be very sensitive to the definition of the preferential tariff margin.